Bacteria Are New Targets for Inhibitors of Human Farnesyltransferase - Weber, Lea; Hagemann, Anna; Kaltenhäuser, Jila; Besser, Manuela; Rockenfeller, Patrick; Ehrhardt, Anja; Stuermer, Ewa; Bachmann, Hagen Sjard (Frontiers in Microbiology, 2021)
Farnesyltransferase inhibitors (FTIs) are focus for the treatment of several diseases, particularly in the field of cancer therapy. Their potential, however, goes even further, as a number of studies have evaluated FTIs for the treatment of infectious diseases such as malaria, African sleeping sickness, leishmaniosis and hepatitis D virus infection. Little is known about protein prenylation mechanisms in human pathogens. However, disruption of IspA, a gene encoding the geranyltranstransferase of Staphylococcus aureus leads to reprogramming of cellular behaviour as well as impaired growth and decreased resistance to cell wall-targeting antibiotics. We used an agar well diffusion assay and a time kill assay and determined the minimum inhibitory concentrations of the FTIs lonafarnib and tipifarnib. Additionally, we conducted cell viability assays. We aimed to characterize the effect of these FTIs on Staphylococcus aureus (S. aureus), methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus epidermidis (S. epidermidis), Escherichia coli (E. coli), E. faecium (E. faecium), Klebsiella pneumonia (K. pneumoniae), Pseudomonas aeruginosa (P. aeruginosa) and Streptococcus pneumoniae (S. pneumoniae). Both the FTIs lonafarnib and tipifarnib were capable of inhibiting the growth of the Gram-positive bacteria Staphylococcus aureus, MRSA, Staphylococcus epidermidis and S. pneumoniae, whereas no effect was observed on Gram-negative bacteria. The analysis of the impact of lonafarnib and tipifarnib on common human pathogens might lead to novel insights into their defence mechanisms and therefore provide new therapeutic targets for antibiotic-resistant bacterial infections.